2018
DOI: 10.1016/j.ejpb.2018.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Selective staining and eradication of cancer cells by protein-carrying DARPin-functionalized liposomes

Abstract: Since their discovery, liposomes have been widely employed in biomedical research. These nano-size spherical vesicles consisting one or few phospholipid bilayers surrounding an aqueous core are capable of carrying a wide variety of bioactive compounds, including drugs, peptides, nucleic acids, proteins and others. Despite considerable success achieved in synthesis of liposome constructs containing bioactive compounds, preparation of ligand-targeted liposomes comprising large quantities of encapsulated proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…Previously we have shown that liposomes functionalized with HER2-specific DARPin can be an effective vehicle for proteins delivery to cancer cells [ 28 ]. Here we used this method for the preparation of ligand-targeted liposomes comprising large quantities of encapsulated toxic protein for the treatment of HER2-positive cancer in vivo.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously we have shown that liposomes functionalized with HER2-specific DARPin can be an effective vehicle for proteins delivery to cancer cells [ 28 ]. Here we used this method for the preparation of ligand-targeted liposomes comprising large quantities of encapsulated toxic protein for the treatment of HER2-positive cancer in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Ribonuclease Bn from B. amyloliquefaciens [ 29 ] was used as a cytotoxic moiety. DARPin and Bn genes were expressed in Escherichia coli BL21(DE3) strain as described by us previously [ 24 , 28 ]. RNAse activity of purified Bn was determined using the acid-insoluble RNA precipitate method [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…DARPin was also attached to nanostructures via maleimide conjugation. This method was utilized for DARPin 9_29 conjugation with the surface of ETA-containing liposomes functionalized using Trout's reagent [87].…”
Section: Application Of Darpins In Nanoparticle Deliverymentioning
confidence: 99%